Mitochondrial function modulates touch signalling in Arabidopsis thaliana. (22nd January 2019) - Xu, Yue; Berkowitz, Oliver; Narsai, Reena; De Clercq, Inge; Hooi, Michelle; Bulone, Vincent; Van Breusegem, Frank; Whelan, James; Wang, Yan
Summary: Plants respond to short‐ and long‐term mechanical stimuli, via altered transcript abundance and growth respectively. Jasmonate, gibberellic acid and calcium have been implicated in mediating responses to mechanical stimuli. Previously it has been shown that the transcript abundance for the outer mitochondrial membrane protein of 66 kDa (OM66), is induced several fold after 30 min in response to touch. Therefore, the effect of mitochondrial function on the response to mechanical stimulation by touch at 30 min was investigated. Twenty‐five mutants targeting mitochondrial function or regulators revealed that all affected the touch transcriptome. Double and triple mutants revealed synergistic or antagonistic effects following the observed responses in the single mutants. Changes in the touch‐responsive transcriptome were localised, recurring with repeated rounds of stimulus. The gene expression kinetics after repeated touch were complex, displaying five distinct patterns. These transcriptomic responses were altered by some regulators of mitochondrial retrograde signalling, such as cyclic dependent protein kinase E1, a kinase protein in the mediator complex, and KIN10 (SnRK1 − sucrose non‐fermenting related protein kinase 1), revealing an overlap between the touch response and mitochondrial stress signalling and alternative mitochondrial metabolic pathways. Regulatory network analyses revealed touch‐induced stress responses and suppressed growth and biosynthetic processes. Interaction with the phytohormone signalling pathways indicated that ethylene and gibberellic acid had the greatest effect. Hormone measurements revealed that mutations of genes that encoded mitochondrial proteins altered hormone concentrations. Mitochondrial function modulates touch‐induced changes in gene expression directly through altered regulatory networks, and indirectly via altering hormonal levels. Significance Statement: Previously it was shown that transcript abundance for the stress‐induced outer mitochondrial membrane protein of 66 kDa (OM66) was rapidly induced several fold in response to touch. A comprehensive study using a variety of mutants that encoded mitochondrial proteins, defence signalling mutants, kinetic, transcriptome and network analyses, revealed that mitochondrial function modulates touch‐induced changes in gene expression directly through altered complex regulatory networks, and indirectly via change in hormonal levels.